Interventions for Improving Adherence and Retention in HIV-Infected Women on ART During Antenatal and Postnatal Care: A Systematic Review - Hoosen, Nikhat (Department of Public Health and Family Medicine, 2021)
Introduction Universal access to antiretroviral therapy (ART) during pregnancy and breastfeeding has implications for retention in HIV care and adherence to ART. Retention and adherence may be especially challenging during antenatal and postnatal periods, where women living with HIV have competing responsibilities between infant care, self-care and personal responsibilities. Lifelong ART also highlights the role interconception care (ICC) and preconception care (PCC) interventions can play in improving maternal outcomes. While the latter exist for other health topics, ICC and PCC interventions targeting women living with HIV has the potential to maintain retention in care and adherence to ART during, after, and in between pregnancies. This systematic review evaluates interventions that aim to improve retention and adherence in pregnant and postpartum women. Methods The Cochrane Library; MEDLINE via PubMed; Web of Science; and EBSCOHOST (Africa Wide, Academic Search Premier, CINAHL, PsychArticles, Health Source Nursing Academic, PsychInfo) and conference databases were searched for articles in English published between 1990 to 2020. All study designs, intervention types and geographic locations were included. Data were extracted using a standardized tool, and effect sizes recalculated for all studies. Risk of bias was conducted using tools suited to specific study designs, and the PRECIS-2 tool assessed intervention applicability in real-world settings. The protocol was registered with PROSPERO (ID: CRD42020185196). Results Thirty-one studies were identified, of which 31 and 16 provided retention and adherence data, respectively. No interconception or preconception care interventions were found. Interventions were predominantly from Sub-Saharan Africa, except one from the USA. Intervention types varied and included integration of services, peer support, mhealth and multicomponent interventions. The definitions of retention and adherence used for outcome assessment varied widely across studies, but almost all were scored as pragmatic in real-world settings. Due to high heterogeneity, a narrative approach was used based on study reported data and the effect sizes. Conclusion Overall, heterogeneity of identified studies make definitive recommendations for interventions scale up difficult. Future interventions will benefit from consistent study designs, outcome definitions, outcome measurements, validated tools, and longer retention time points will strengthen the evidence base. Ongoing studies being conducted show promise in addressing some of these points.